A política cultural francesa e o Lyceu Franco-Brasileiro de S. Paulo como um modelo de ensino secundário para o Brasil – (1916 - 1951) - Kovacevic, Gisele Schiavetti Basilio (2019)
This dissertation has as its object the Liceu Franco-Brasileiro de S. Paulo and analyses the process of its constitution, comprising the organizational and school culture. The period studied contemplates the first aspirations of the institution, from 1916, until 1951, when it underwent a significant reform that culminated in changes that involved from its architectural structure to pedagogical project. For this analysis, we enrol as the main source the reports and correspondence produced within the Ministry of Foreign Affairs of France and currently placed in the French National Archives. As a complementary source, we mobilized the publications of the newspaper O Estado de S. Paulo available in its digital collection. The owners of the journal not only disseminated news and information about the high school but were also involved in its creation. In addition, as an analytical aid, we relied on the history of the institution and on prosopographic studies about the actors involved in its conception and development. The research revealed that these subjects aspired to a project of secondary education educational institution between the creation of the University of São Paulo, with the purpose of offering a model education for those who, supposedly, in the future would be students of this higher education institution. As the main theoreticalmethodological reference, we rely on Justino Magalhães' proposals and on the social project he aimed to legitimize, articulated to different networks of sociability, this category being analysed in line with the definitions of Jean-François Sirinelli